Pengaruh Persepsi Tentang Peran Kepala Sekolah Terhadap Kinerja Guru di Madrasah - Nana Suyadi (DIMAR: Jurnal Pendidikan Islam, 2019)
Education gives a very large contribution to the progress of a nation, and a vehicle in national character building. This condition is requires the participation of people to contribute in improving quality of education in schools. Community participation in improving the quality of education in schools can be realized in the form of independent agencies called the school committee. Besides requiring community participation through school committees, improving the quality of education in schools can not be separated from the role played by the school leaders, both roles related to managerial tasks, education, administration, and supervision.The problem formulation of this research: “Are there influence of perception of teachers about the role of school leader and School Committee toward performance of teachers Madrasah Aliyah in Bandar Mataram, District Central Lampung ? The purpose of this research is to know the Influence of Teacher Perceptions about The role of school leaders and School Committee toward performance of teachers Madrasah Aliyah in Bandar Mataram, District Central Lampung